Higher order thinking skills (hots) among high, moderate and low achieving learners in learning the periodic table of elements - Si, Hui Ling (Universiti Malaysia Sarawak (UNIMAS), 2015)
Enhancing student's thinking ability is one of the objectives of the national education system. In order to accomplish the goal, the priority should be placed on thinking skills in the teaching and learning processess in order to develop the 21 51 century thinkers that our world needs. A thoughtful learning foundation emphasises thinking skills in teaching and learning. Additionally, the content in Chemistry learning is replete with various abstract concepts and therefore it requires intellectual thought and understanding. The purpose of this study is to explore the higher order thinking skills (HOTS) among high, moderate, and low achieving learners in learning the Periodic Table of Elements. The study adopts a qualitative approach to achieve its purpose. The think aloud method and semi-structured interviews are used to get an in-depth understanding of HOTS among the three categories of learners. A total of 14 Form 4 pure science students from SMK Tinggi Kuching, Sarawak participated in this study. In order to explore HOTS among the three categories of learners, the students are asked to answer the questions (Structured type) which encompass the six categories of cognitive processes based on the revised Bloom's taxonomy. The result of the study, found that the high achieving learners possess all the higher order skills that are analysing, evaluating and creating. The moderate achieving learners possess the analysing and evaluating skills, whereas the low achieving learners, at least possess one of the higher order skills of analysing. The findings suggest that teachers should teach HOTS to the students of different academic levels. The findings of the study hopefully could also provide insights to educators to come out with various practical tools for helping students to accomplish tasks requiring higher order thinking.